(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article describes poetical similarities in the sonnets of English poet Edmund Spenser and Ukrainian poet Ivan Franko (collection «Z vershin I nizin»). The author characterizes the particular virtues of reception, the social function of the poetry, the role of poets in literature, and the value of human life. She also depicts the relationship between nature and man. Furthermore she explains the priority of civil ideals and love.